Of negotiations, strategies and ethical projects: Inheriting memories of violence among Syrian mothers in displacement - Magdalena Suerbaum (Antropologia)
This article centres on Syrian women’s narratives and practices of intergenerational knowledge transmission on violence. Based on data collected over the course of fourteen months of ethnographic research in Istanbul and Berlin in 2022/2023, this article questions how experiences of violence are remembered vis-à-vis one’s children who are raised in displacement. Syrian women’s modes and practices of communicating violent experiences feature as complex negotiations and thoughtful strategies. Children play an active role in the process of intergenerational knowledge transmission. Centring on verbal and non-verbal acts of sharing of memories, this article suggests thinking of them as ambivalent balancing acts and ethical projects directed at a liveable life for one’s offspring, the next generation and Syrian society within and beyond the nation’s borders.